Outcomes of Patients With Thyroid Eye Disease Partially Treated With Teprotumumab. Issue 2 (9th September 2022) - Ho, Tiffany C.; Maamari, Robi N.; Kossler, Andrea L.; Sears, Connie M.; Freitag, Suzanne K.; Reshef, Edith R.; Shinder, Roman; Rootman, Daniel B.; Diniz, Stefania B.; Kahana, Alon; Schlachter, Dianne; Do, Thai H.; et al.
Abstract : Purpose: In response to the coronavirus (COVID-19) pandemic, teprotumumab production was temporarily halted with resources diverted toward vaccine production. Many patients who initiated treatment with teprotumumab for thyroid eye disease were forced to deviate from the standard protocol. This study investigates the response of teprotumumab when patients receive fewer than the standard 8-dose regimen. Methods: This observational cross-sectional cohort study included patients from 15 institutions with active or minimal to no clinical activity thyroid eye disease treated with the standard teprotumumab infusion protocol. Patients were included if they had completed at least 1 teprotumumab infusion and had not yet completed all 8 planned infusions. Data were collected before teprotumumab initiation, within 3 weeks of last dose before interruption, and at the visit before teprotumumab reinitiation. The primary outcome measure was reduction in proptosis more than 2 mm. Secondary outcome measures included change in clinical activity score (CAS), extraocular motility restriction, margin reflex distance-1 (MRD1), and reported adverse events. Results: The study included 74 patients. Mean age was 57.8 years, and 77% were female. There were 62 active and 12 minimal to no clinical activity patients. Patients completed an average of 4.2 teprotumumab infusions before interruption. A significant mean reduction in proptosis (–2.9 mm in active and –2.8 mm in minimal to no clinical activity patients, P < 0.01) was noted and maintained during interruption. For active patients, a 3.4-point reduction in CAS ( P < 0.01) and reduction in ocular motility restriction ( P < 0.01) were maintained during interruption. Conclusions: Patients partially treated with teprotumumab achieve significant reduction in proptosis, CAS, and extraocular muscle restriction and maintain these improvements through the period of interruption. Abstract : Despite a national teprotumumab shortage resulting from COVID-19 pandemic, patients who were partially treated with teprotumumab achieve significant reduction in proptosis, clinical activity score, and extraocular muscle restriction and maintain these improvements during short-term interruption.